Price Disparity of Dual-Listed Companies (DLCs) in the Equity Market : Evidence from Indian Bourses with Special Reference to the Pharma Sector - Muthu Pandian, B.; Vishal, Ravi Shekhar (Indian Journal of Research in Capital Markets, 2019)
The equity market in India has shown high level of reporting price differences of dual-listing companies (DLCs) in the leading stock exchanges of India (i.e. Bombay Stock Exchange and National Stock Exchange) and depicted high price disparity. The present study intended to measure the price disparity that existed between the dual listed securities in the equity market with special reference to the pharma sector. The present study included the top four pharmaceutical companies which are traded on the BSE & NSE, such as: Sun Pharmaceutical's Ltd., Lupin, Dr. Reddy's Laboratories, and Cipla. The daily open-high-low-close (OHLC) price data were extracted from end of the day (EOD) series published by the respective exchanges through their official websites. After the basic data cleaning process, the descriptive statistics were used to find the price disparity. In addition to this, histogram was used to measure the price variance. The results of the study revealed that among the four pharma companies, Dr. Reddy's Laboratories had the highest price disparity during the study period. It also showed that the reporting price disparity was huge in case of Dr. Reddy's Laboratories as compared to the remaining companies after currency demonetization.